2020
DOI: 10.1039/d0ra04748a
|View full text |Cite
|
Sign up to set email alerts
|

Modular design and self-assembly of multidomain peptides towards cytocompatible supramolecular cell penetrating nanofibers

Abstract: In this work, we demonstrated a facile supramolecular approach based on modularly designed multi-domain peptides to construct peptide-based nanomaterials with intrinsic cell penetrating activity and excellent cytocompatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…This peptide is known to self-assemble into a sandwich-like β-sheet nanofiber in which the hydrophobic residues are buried within the sandwich structure and shielded from the aqueous environment. [43][44][45][46][47] By replacing some of the hydrophobic residues on MDPs with these ionizable amino acids, nanofibers with an ionizable hydrophobic core can be generated to undergo pH-induced self-assembly or disassembly. While the pK a of a free tertiary amine is typically found in the basic region, we anticipate the local hydrophobic environment can shift the pK a of these tertiary-amine containing residues toward the biologically relevant pH at a near neutral or weakly acidic range, which is critical for practical applications such as tumor-acidity targeted drug delivery or proton transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This peptide is known to self-assemble into a sandwich-like β-sheet nanofiber in which the hydrophobic residues are buried within the sandwich structure and shielded from the aqueous environment. [43][44][45][46][47] By replacing some of the hydrophobic residues on MDPs with these ionizable amino acids, nanofibers with an ionizable hydrophobic core can be generated to undergo pH-induced self-assembly or disassembly. While the pK a of a free tertiary amine is typically found in the basic region, we anticipate the local hydrophobic environment can shift the pK a of these tertiary-amine containing residues toward the biologically relevant pH at a near neutral or weakly acidic range, which is critical for practical applications such as tumor-acidity targeted drug delivery or proton transport.…”
Section: Introductionmentioning
confidence: 99%
“…As a proof‐of‐concept demonstration, we introduced these residues in a multidomain peptide (MDP). This peptide is known to self‐assemble into a sandwich‐like β‐sheet nanofiber in which the hydrophobic residues are buried within the sandwich structure and shielded from the aqueous environment [43–47] . By replacing some of the hydrophobic residues on MDPs with these ionizable amino acids, nanofibers with an ionizable hydrophobic core can be generated to undergo pH‐induced self‐assembly or disassembly.…”
Section: Introductionmentioning
confidence: 99%
“…Most NPs are internalized by cells using endocytic or phagocytic pathways, including clathrin, caveolin, micropinocytosis, and other energy-independent pathways. Previous studies have showed that self-assembled NFs undergo cell uptake by micropinocytosis in HeLa cells . Given the new structure and composition of NCs, we screened the NCs for their uptake mechanisms using various endocytosis inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescein terminated peptides were synthesized as previously described by Yang and Dong . 5(6)-Carboxyl fluorescein (FITC)-tagged peptides were mixed with Rho B PLGA NPs.…”
Section: Methodsmentioning
confidence: 99%
“…As aforementioned, biopolymer PEMCs are attractive in terms of their potential to mimic the extracellular matrix (ECM) as well as host bioactive molecules. Single-and multi-domain peptides (SDPs and MDPs, respectively) are emerging as materials for use in tissue engineering/regeneration applications within the development of nanofibrous scaffolds [258,259]. The incorporation of these bioactive-mimicking SDP/MDPs into PEMCs are of interest.…”
Section: Functionalisation With Ligands and Antibodiesmentioning
confidence: 99%